Biology is technology : the promise, peril, and new business of engineering life - Carlson, Robert H., 1970- (Harvard University Press, 2010)
In Biology Is Technology, author Robert Carlson offers a uniquely informed perspective on the endeavors that contribute to current progress in the science of biological systems and the technology used to manipulate them.